2004
DOI: 10.1097/01.mlr.0000135809.92048.d9
|View full text |Cite
|
Sign up to set email alerts
|

Physician Process and Patient Outcome Measures for Diabetes Care

Abstract: Healthcare organizations can adopt many of the identified organizational characteristics to enhance the delivery of care in their settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 46 publications
0
42
0
1
Order By: Relevance
“…A study in the American Veterans' Administration found that the availability of a "champion" for use of clinical guidelines and the distribution of audit results to primary providers were associated with better processes of care. They also found that feedback to providers and grand rounds presentations were associated with improved patient intermediate outcomes (10). As a result of SDPI funding, diabetes coordinators and teams at each facility act as "champions" and facilitate distribution of audit results to clinical providers.…”
Section: Discussionmentioning
confidence: 99%
“…A study in the American Veterans' Administration found that the availability of a "champion" for use of clinical guidelines and the distribution of audit results to primary providers were associated with better processes of care. They also found that feedback to providers and grand rounds presentations were associated with improved patient intermediate outcomes (10). As a result of SDPI funding, diabetes coordinators and teams at each facility act as "champions" and facilitate distribution of audit results to clinical providers.…”
Section: Discussionmentioning
confidence: 99%
“…Singh & Kalavar (213) reported similar findings. Ward et al (256) observed that the VA's better adherence with diabetes care guidelines was associated with frequent feedback to frontline caregivers, more effective communication between physicians and nurses, and other organizational characteristics. Proper management of diabetes is especially important for the VA because more than 25% of its patients are diabetic, and this population has an exceptionally high rate of comorbidity and use of health care services (10).…”
Section: Wwwannualreviewsorg • Extreme Makeovermentioning
confidence: 99%
“…Thirty-five percent of the participants in a community-based study did not follow the vision care guidelines (9). Among the 109 Veterans Affairs medical centers, adherence to the annual eye screening recommendation varies from 48 to 93% (mean Ϯ SD 69.1 Ϯ 10.3%) (10). Only 54% of the patients with diabetes in the Walter Reed Health Care System receive an annual retinal examination.…”
mentioning
confidence: 99%